Flux and Rejection of Amine Using Membrane Process - Ahmad, Fathin Fathiha (Universiti Teknologi PETRONAS, 2010)
Aliphatic amines are widely used as raw materials in much industrial process, and very harmful chemical species constituting the focus ofmany environmental concerns. The objectives ofthis project are to study the separation behavior of amine from natural gas purification plant using membrane process, to investigate and study the factors that affecting the performing of separation amine. Amine chose in this project is Triethanolamine, TEA, which is a tertiary amine. In refinery gas treatment plant, amine absorbed acid gas components, hydrogen sulfide, H2S and carbon dioxide, C02. H2S and C02 are absorbed by the amine solution and the sweet gas leaves the absorber. Once stripped of contaminants, amine solution is reused. Asuggested method to study the separation ofamine is through membrane separation. The factors affecting the membrane performance are operating pressure, feed concentration, temperature, pH, concentration and cross flow velocity. Membrane performance is analyzed based on the flux or rejection/ separation ofamine. Generally, the separation of amine from wastewater using membrane system could be implemented for industrial applications but with several modifications oftransport and parameters that had to be studied further in order to achieve optimum results in the industry application. The effect of different parameters in membrane performance will be observed and evaluated. The acquired results will be used for comparison of the importance of experimental parameters in optimization of amines separation. The flux was increased as operating pressure increased. Similarly, flux increased as velocity increased. CA202 has highest flux (104L/m2.h), followed by AFC40 and lowest was AFC99 (0.5L/m2.h). From the analysis and feasibility study, the membrane separation process is a good separation method in water treatment. AFC99 showed better result than AFC40 and CA202. AFC99 almost removed 89%of amine, compared to AFC40, 69%and CA202 49%. Further analysis need to be done by using several methods, techniques and other considerations should be taken in order to achieve the project objectives.